FANATISME MAZHAB DI LINGKUNGAN PESANTREN; STUDI KASUS DI PESANTREN MUSTHAFAWIYAH PURBA BARU - Muhammad Arsad Nasution (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2022)
School fanaticism often colors the students in the pesantren environment which produces graduate who only tend to recognize the primacy and validity of certain schools of thought. As a result of the fanaticism of the school of thought can lead to disharmony between fellow Muslims in carrying out the teachings of Islam itself. Indications of mazhab fanaticism appear in the Musthafawiah Purba Baru Islamic Boarding School. The fanaticism of this school is influenced by fiqh learning that focuses on certain schools, namely the Safi'yah school of jurisprudence, the influence of teachers who are from the Shafi'iyah school, and the policy of establishing a pesantren that limits itself to learning fiqh with the Syafi'iah school.